ナンキョク タイリク カスミイワ ロガン チタイ ノ ケイソウ ショクセイ - 福島, 博; フクシマ, ヒロシ; FUKUSHIMA, Hiroshi (国立極地研究所, 1962)
P(論文) The Kasumi Rock Ice-Free Area is located at 68°21'5"1.S. and 42°15'13"1.E. This area seems to have experienced not so many years since the glacial epoch, as no evidence of weathering nor weathered rocks were found there. Moss and lichen were not seen either. Only moraines were found in some places. 30 algae samples from 8 ponds were collected in polyethylene bottles. The time available for detailed investigation of the environmental factors was too short. The result is outlined in Table 1. The investigated ponds are 10-100 meters in diameter and less than 60cm in depth. The contents of nutritious salts (P, NH_3, N0_2) in these ponds are so small that a quantitative analysis was impossible, just like the case of the Shin-nan Rock Area. The SiO_2 content was 19-20 mg/l (standard). Ponds in the Kasumi Rock Area can be classified into two groups, one is of fresh water ponds and the other is of brackish water ponds. The former includes Stations 1 and 8, and the other has 5 stations (Stations 2-7). Concerning PH, the former was a little acidic and the latter was alkaline. The Kasumi Rock fresh water ponds contain much more Chlor ion than those of the Shin-nan Rock Area. Station 1 has 358 mg/l Chlor ion. In the brackish water ponds, the Chlor ion content varies with pond, and ranges from 4,959 to 9,523 mg/l. This is ca. 1/2-1/4 of Chlor ion in sea water. Almost all these brackish water ponds contain hydrogen sulfide and have a smell. Their bottom mud is black. In the ponds of the Kasumi Rock Area, blue-green algae and diatoms are predominant, whereas in the Shin-nan Rock Area only blue-green algae are found. The algal vegetation at Kasumi Rock is characterized by diatoms: Diatoms flora of the fresh water ponds differs from that of the brackish water ponds. The former belongs to the Navicula muticopsis association, and the latter to the Navicula cryptocephala var. intermedia-Navicula cryptocephala-Tropidoneis laevissima association. The writer found 46 taxon of diatoms in these ponds. Among 34 taxon already ...